ANALISIS SOFT SKILL DAN HARD SKILL SERTA PENGARUHNYA TERHADAP OPTIMISME CALON LULUSAN PRODI MANAJEMEN UNIHAZ BENGKULU - Fauzan Fauzan (Creative Research Management Journal, 2020)
This research is explanatory research, intended to determine the relationship between soft skill and hard skill variables on the optimism of prospective graduates of Bengkulu Unihaz Management Study Program. The quantitative data of this study were obtained from questionnaires which were then processed into statistical analysis. The results of the analysis are known soft skill variables (X1) and hard skills (X2) have a strong and unidirectional relationship, and have a positive effect on the optimism variable of prospective graduates of the Unihaz Bengkulu study program. This is evidenced by the value of multiple correlation, multiple linear regression, t-test and f-test. Of the two independent variables hard skill contribution is greater than the soft skill. As a suggestion to improve students' hard skills and soft skills, they encourage them to be more active in research and community service, carry out excursion studies, namely visiting companies, entrepreneurs, crafts and other institutions that can foster their hard skills and soft skills, then directed to be more active in student organizations, youth and spirituality.